Chronic Kidney Disease Care in Indonesia: Challenges and Opportunities - Ni Made Hustrini (Interna Publishing, 2023)
The burden of chronic kidney disease (CKD) is a significant global health concern. Previous study reported that the CKD incidence reached 200 cases per million per year in many countries with the prevalence 11.5% (4.8% in stages 1-2 and 6.7% in stages 3-5). Other study further reported that the estimate prevalence of CKD was 15% higher in low- and middle-income countries compared to the high-income countries. However, there are limited statistics available on the epidemiology of CKD in Indonesia. According to the Basic Health Research (Riset Kesehatan Dasar [Riskesdas], 2018], the prevalence of CKD in Indonesia increased from 0.2% in 2013 to 0.3% in 2018. These results may understate the true prevalence of CKD in our population. Despite the limited data on the CKD prevalence, the number of patients receiving kidney replacement treatment (KRT), primarily in the form of hemodialysis, is rapidly rising (i.e., more than 132.000 in 2018). A comprehensive nephrology referral system is also a challenge. We can argue this statement with evidence from the tertiary care, where it was reported that most kidney failure patients (83%) commenced dialysis with an urgent start, along with late referral to nephrologist (90%), started dialysis with temporary catheter (95.2%), and the median eGFR to start dialysis was 5.3 (range: 0.6 - 14.6) ml/minute/1.73 m2. However, individual awareness, as well as an effective screening and prevention program for high-risk group are also a significant hurdles.  Since 2022, the Ministry of Health has initiated a health transformation program to improve the health system, to address health disparities, both within the country and between countries. One of the health transformation programs which specify in nephrology care is the implementation of the Uro-Nephrology Support Program (Program Pengampuan Uro-Nefrologi), with the aim to strengthen services, provide equal distribution of services and increase the latest technology for the diagnosis and treatment of urology/nephrology diseases in Indonesia. This program included secondary and tertiary care to improve the extent and quality of care to slowing the CKD progression, improving kidney replacement therapy (hemodialysis, peritoneal dialysis, and kidney transplant) access and treatment, as well as to provide dialysis training program for health care workers. Providing high-quality nephrology care that all Indonesians can access is challenging. Yet, steps have already been taken in the direction of service enhancement. Thus, there is hope for better kidney health in Indonesia. Governments, academic medical centres, nephrology societies, as well as the citizen will all need to work together and take consistent effort to make a sustainable and comprehensive kidney care.